Myoferlin plays a key role in VEGFA secretion and impacts tumor‐associated angiogenesis in human pancreas cancer. Issue 3 (8th September 2015) - Fahmy, Karim; Gonzalez, Arnaud; Arafa, Mohammad; Peixoto, Paul; Bellahcène, Akeila; Turtoi, Andrei; Delvenne, Philippe; Thiry, Marc; Castronovo, Vincent; Peulen, Olivier
Abstract : Pancreatic ductal adenocarcinoma is one of the most deadly forms of cancers with no satisfactory treatment to date. Recent studies have identified myoferlin, a ferlin family member, in human pancreas adenocarcinoma where its expression was associated to a bad prognosis. However, the function of myoferlin in pancreas adenocarcinoma has not been reported. In other cell types, myoferlin is involved in several key plasma membrane processes such as fusion, repair, endocytosis and tyrosine kinase receptor activity. In this study, we showed that myoferlin silencing in BxPC‐3 human pancreatic cancer cells resulted in the inhibition of cell proliferation in vitro and in a significant reduction of the tumor volume in chick chorioallantoic membrane assay. In addition to be smaller, the tumors formed by the myoferlin‐silenced cells showed a marked absence of functional blood vessels. We further demonstrated that this effect was due, at least in part, to an inhibition of VEGFA secretion by BxPC‐3 myoferlin‐silenced cells. Using immunofluorescence and electron microscopy, we linked the decreased VEGFA secretion to an impairment of VEGFA exocytosis. The clinical relevance of our results was further strengthened by a significant correlation between myoferlin expression in a series of human pancreatic malignant lesions and their angiogenic status evaluated by the determination of the blood vessel density. Abstract : What's new? New results have uncovered a function of a key pancreatic cancer protein. Myoferlin, a phospholipid‐binding protein, is overexpressed in several cancers, including pancreatic adenocarcinoma. In this paper, the authors report that when they stop the production of myoferlin in pancreatic tumor cells, the tumors are smaller and have fewer blood vessels than usual. Then, using a pancreatic tumor database and a tissue bank, they looked at myoferlin expression in human pancreatic cancer patients. Those tumors expressing myoferlin had higher density of blood vessels, and poorer survival, than other cancers. Thus, myoferlin seems a promising target to treat one of the deadliest human cancers.